160k views
6 votes
Nth term of -7 -6 -3 2 9 18 29

1 Answer

9 votes

Answer:

n^2 - 2n - 6.

Explanation:

The difference between terms is

1 3 5 7 9 11 which is an arithmetic sequence with common difference 2.

The given series is quadratic and the nth term will contain n^2.

n = 1 2 3 4 5

n^2 = 1 4 9 16 25

term = -7 -6 -3 2 9 Subtract these from the n^2 values:

Subtract: 8 10 12 14 16

The last row is an A.S. with nth term 8 + 2(n - 1) = 6 + 2n

So the required nth term = n^2 - (6 + 2n)

= n^2 - 2n - 6.

User NewbNox
by
4.9k points